In Vivo Synergistic Anti-Inflammatory Action of Rutin and Quercetin using Rat Model - Prashant S. Kumbhar; Bimlesh Kumar; A.P.Gadad; Shiom Mane; Samarth Giri; Dr.S.C.Burli; Priyanka Kamble; Shivani Patil; Abhijeet Shirguppe (International Journal of Medical Toxicology and Legal Medicine, 2024)
Inflammation is a complex biological process concerning various cellular and molecular mediators, often leading to significant damage to the tissue. Anti-inflammatory medications have become crucial for treating inflammatory disorders, but the development of drug resistance and undesirable side effects has made the quest for complementary or alternative therapies important. This study aimed to investigate the possible synergistic anti-inflammatory effects of quercetin as well as rutin, two flavonoids with established antioxidant properties, when combined with Diclofenac in an in vivo model. Rats were used in the study to assess the anti-inflammatory possessions of quercetin and rutin utilizing a variety of models, including paw edema produced by carrageenan, climbing staircases, and motility tests. The findings demonstrated quercetin’s and rutin’s strong anti-inflammatory properties, with the combination therapy having beneficial benefits. Rutin and quercetin together significantly reduced paw oedema in the carrageenan- influenced paw oedema model, almost equal to the effectiveness of diclofenac. In the staircase climbing activity, significant recovery was seen when quercetin and rutin were combined; this indicated a synergistic effect and was almost as effective as diclofenac. In the motility test, the anti-inflammatory properties of quercetin along with rutin were separately evident, but the combination significantly reduced inflammation. The results suggest that rutin and quercetin, especially when taken together, are effective anti-inflammatory treatment options that can effectively reduce inflammation and its related mobility deficits. Further exploration and potential clinical application of rutin and quercetin as therapeutic agents for inflammatory conditions are supported.